Respuesta :

Answer:

(g-f)(10) = - 71

Step-by-step explanation:

f(x) = x² - 1

g(x) = 2x + 8

To find (g-f)(10) first find ( g - f)(x)

To find ( g - f)(x) subtract f(x) from g(x)

That's

( g - f)(x) = 2x + 8 - ( x² - 1)

Remove the bracket

( g - f)(x) = 2x + 8 - x² + 1

Simplify

( g - f)(x) = - x² + 2x + 9

To find (g-f)(10) substitute the value in the bracket that's 10 into ( g - f)(x)

That is

(g-f)(10) = -(10)² + 2(10) + 9

= - 100 + 20 + 9

= - 100 + 29

= - 71

Hope this helps you

ACCESS MORE